2017
DOI: 10.1556/2006.6.2017.051
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of personality traits in impulsivity-related disorders: From substance use disorders and gambling disorder to bulimia nervosa

Abstract: Background and aimsThe main aim of this study was to analyze and describe the clinical characteristics and shared personality traits in different impulsivity–compulsivity spectrum disorders: substance use disorders (SUD), gambling disorder (GD), and bulimia nervosa (BN). The specific aims were to compare personality differences among individuals with pure SUD, BN with and without SUD, and GD with and without SUD. In addition, we assessed the differential predictive capacity of clinical and personality variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 71 publications
6
32
1
Order By: Relevance
“…Interestingly, there were no differences between the two groups on any of the temperament or character dimensions assessed. This result is contrary to previous findings (Claes et al, 2012;del Pino-Gutiérrez et al, 2017;Farstad et al, 2016;Jiménez-Murcia et al, 2013. A potential reason could be that the relationship in temperament/character between binge/purge type eating disorder and gambling disorder is moderated by gender (Alvarez-Moya et al, 2007).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Interestingly, there were no differences between the two groups on any of the temperament or character dimensions assessed. This result is contrary to previous findings (Claes et al, 2012;del Pino-Gutiérrez et al, 2017;Farstad et al, 2016;Jiménez-Murcia et al, 2013. A potential reason could be that the relationship in temperament/character between binge/purge type eating disorder and gambling disorder is moderated by gender (Alvarez-Moya et al, 2007).…”
Section: Discussioncontrasting
confidence: 94%
“…More importantly from a clinical perspective, little is known about the psychiatric and personality correlates that differentiate people with comorbid binge/purge type eating disorder and gambling disorder from those without, knowledge that may help in tailoring unique treatment approaches among this dual-diagnosis population. Indeed, although previous research by Jiménez-Murcia and colleagues (e.g., Claes et al, 2012;del Pino-Gutiérrez et al, 2017;Jiménez-Murcia et al, 2013 has delineated important differences in the comorbid relationship between binge/purge type eating disorders, it has focused predominately on personality dimensions among people seeking treatment for eating disorder (for an exception, see Jiménez-Murcia et al, 2017). Little is known about clinical correlates (e.g., psychiatric comorbidities and symptom severity) in this dual-diagnosis population, especially among people seeking treatment for gambling disorder.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, also in the HC group, this association was limited to male subjects, suggesting a gene x sex effect in the determination of NS levels. More in detail, we found that the Val/Val genotype was associated with higher NS levels in this subgroup of subjects, partially consistent with literature data about the effects of this genotype on impulsivity and addictive behaviors [64, 65], which are both associated with NS dimensions [66, 67]. Furthermore, the lack of association observed in BD sample may support the hypothesis that BD pathophysiological process alters the neurobiological substrates of NS, as previously stated.…”
Section: Discussionsupporting
confidence: 91%
“…It is often associated with affective disorders (AD) [7], substance use disorders (SUD) [8][9][10][11] and personality disorders (PD) [12][13][14]. It has been hypothesized that these comorbidities-specifically SUD and PD-develop on the basis of an increased impulsivity and affective instability in patients with BN [15][16][17][18]. This view is supported by findings that borderline PD traits are particularly common among patients with BN [19].…”
Section: Bulimia Nervosamentioning
confidence: 99%